Modification of wheelchair function for handicap purpose usage - Zaidie, Rahim (2009)
This report is an outcome of the work I have carried out in doing and completing my final year project, the Modification of Wheelchair Function for Handicap Purpose Usage. The report starts off with an introduction wheelchair concerning of definition of important component of this topic such as definition of optimization, wheel chair and handicap. Then a further describe on the critical part of stress on the wheelchair. In this steps, from the knowledge gathered from the questionnaire is use to make a design refers to case data that suitable for the project. Several sketches have been made and only a few have been selected based on the suitability design. Based on the sketches, material needed in this project will be listed and suitable design will be selected. Next all the sketches will be draw into Solidworks 2006 software. Then, go through to simulation process by using FEA tools that is ALGOR software, the design was analyzed using constant force. Improvement of critical part of seating support and front tire design was compared based on material used, analysis on Stress Von Mises. At the end, when all the process mentioned above is done, the material for report writing is gathered. The report writing process will be guided by the Universiti Malaysia Pahang final year report writing guide. This process also included the presentation slide making for the final presentation of the project. The project ended after the submission of the report and the presentation slide has been presented.